A comparative study of the essential oil from flowers and fruits of lepisanthes rubiginosa (Roxb.) Leenh - Chuangbunyat J. (2014)
The essential oils extracted by hydrodistillation from the flowers and fruits of Lepisanthes rubiginosa (Roxb.) Leenh. were analyzed by capillary GC and GC-MS. The major components of the flower essential oil were nerolidol (34.8%), palmitic acid (13.2%) and farnesol (10.0%). For the fruit essential oil, palmitic acid (66.1%), myristic and (10.0%) and linoleic acid (5.5%) appeared to be the major constituents. Evaluation for in vitro anticancer activity of the essential oils was done against three human cancer cell lines (KB-Oral cavity cancer, MCF7 Breast cancer, NCI-H187 Small cell lung cancer). Only the flower essential oil exhibited anticancer activity against NCI-H187. Small cell lung cancer with the IC 50 of 43.90 μgmL -1. The flower essential oil also possessed antioxidant activity (ABTS method) with the % inhibition of 25.4%, whereas the fruit essential oil did not show anticancer activity and possessed low antioxidant activity with the % inhibition of 6.4%. The flower and fruit essential oils exhibited strong antimicrobial activity against Trichophyton mentagophyte and showed moderately activity against Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa and Candida albicans.